2016
DOI: 10.1093/eurpub/ckw025
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of studies in the contributions of the work environment to ischaemic heart disease development

Abstract: Background: There is need for an updated systematic review of associations between occupational exposures and ischaemic heart disease (IHD), using the GRADE system. Methods: Inclusion criteria: (i) publication in English in peer-reviewed journal between 1985 and 2014, (ii) quantified relationship between occupational exposure (psychosocial, organizational, physical and other ergonomic job factors) and IHD outcome, (iii) cohort studies with at least 1000 participants or comparable case-control studies with at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 31 publications
3
105
0
3
Order By: Relevance
“…Job stress measured with this instrument has previously been shown to be associated with and predict physical health across different diseases. [35][36][37] The novel aspect of our study is that, to our knowledge, it is the first to systematically evaluate job stress in a large cohort of patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Job stress measured with this instrument has previously been shown to be associated with and predict physical health across different diseases. [35][36][37] The novel aspect of our study is that, to our knowledge, it is the first to systematically evaluate job stress in a large cohort of patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of coronary disease indicate that these instruments are relatively robust with respect to recall bias. A recent systematic review of high quality studies found similar associations to job strain in case-control and prospective studies (4). Moreover, in a study of myocardial infarction at working age, self-rated and job exposure matrix based assessments of job demands and decision latitude showed similar relations in cases and controls, further supporting a limited influence of recall bias on these measures (37).…”
Section: Psychosocial Work Environment and Strokementioning
confidence: 81%
“…Education and socioeconomic status are consistently reported to be associated with stroke (1), and an association with psychosocial stress has been suggested (2). There is also an accumulating literature suggesting an association between cardiovascular disease and the psychosocial work environment (3)(4)(5). The main body of evidence comes from studies on coronary heart disease, while stroke has been less studied.…”
mentioning
confidence: 99%
“…A similar approach has been applied in a previous study investigating the association between supervisor support and sickness absence in diabetic individuals, using the same cohort studies [32]. Low social support at work was more common among caregivers compared to non-caregivers, which is a noteworthy finding, given the mitigating effect of social support at work on health [33][34][35].…”
Section: Discussionmentioning
confidence: 96%